Interpersonal Relatedness and Non-suicidal Self-Injurious Behaviors in Female Adolescents With Borderline Personality Disorder - Guénolé, Fabian; Spiers, Solène; Gicquel, Ludovic; Delvenne, Veronique; Robin, Marion; Corcos, Maurice; Pham-Scottez, Alexandra; Speranza, Mario (Frontiers in Psychiatry, 2021)
Background: Psychopathological models of adolescent borderline personality disorder (BPD) suggest that non-suicidal self-injuring (NSSI)—a particularly frequent symptom in girls—may constitute a way of coping with distress resulting from interpersonal concerns they typically experience as a developmental psychopathological feature. Objectives: Our objective was to investigate the relationship in BPD female adolescents between NSSI and the Sidney Blatt two-polarities model of personality development, which focuses on the psychological processes of interpersonal relatedness and self-definition. Methods: The study was conducted within the European Research Network on Borderline Personality Disorder in Adolescence, using the Depressive Experience Questionnaire (DEQ). Results: BPD patients (n = 59; mean age = 16.6 ± 1.3) scored significantly higher than healthy controls on the two DEQ sub-factors assessing the more immature forms of Interpersonal Relatedness (Neediness) and Self-definition (Self-criticism) and significantly lower on the more mature form of Self-definition (Efficacy). BPD adolescents with NSSI showed significantly higher scores on both mature and immature forms of Interpersonal Relatedness (Neediness and Connectedness) compared to BPD adolescents without NSSI. A logistic regression analysis showed that the subfactor Neediness of the DEQ was the only significant predictor of the presence of NSSI among BPD adolescents. Conclusions: The preliminary results of this study suggests that NSSI in adolescents with BPD is developmentally linked to high developmental concerns in the domain of interpersonal relatedness, which may be taken into consideration in clinical practice. More studies are necessary to better understand the relationships between NSSI and developmental psychopathology in borderline adolescents.